The combination of inde?nite and de?nite ‘determiners’ — a cross-linguistic study - Duah, Reginald; Grubic, Mira; Renans, Agata (Proceedings of Sinn und Bedeutung, 2021)
In the West African languages Akan, Ga (Kwa), Ngamo, and Hausa (West-Chadic), de?nite familiarity markers and choice-functional inde?nites can combine giving rise to a de?nite interpretation, which poses a puzzle for a compositional analysis of DPs. When combined, three different readings can arise: anaphoric, recognitional, or complement anaphoric reading, though the languages differ with respect to which reading is available. We propose that the available readings depend on (i) whether the de?nite is strongly or weakly familiar, and (ii) whether the choice-functional inde?nite has a novelty condition or not. By that the paper contributes to the ongoing discussion on the interpretation of (in)de?nites, crosslinguistically.